PREVENTION OF EARLY STUNTING THROUGH ADOLESCENT HEALTH COUNSELING FOR STUDENTS AT MULIA HUSADA HEALTH VOCATIONAL SCHOOL - Zakiyah Yasin; Maulana Widi Andrian (Caring : Jurnal Pengabdian Masyarakat, 2022)
The incidence of malnutrition in toddlers is due to lack of attention to nutritional status and management. Nutritional status has a very big influence in realizing quality human resources in the future. Malnutrition is a big problem in Indonesia, although the Government of Indonesia has made efforts to overcome it. The problem of nutritional status in toddlers is still a homework and challenges where what happens is cases of stunting, malnutrition and others, each region is also working together to alleviate this problem which is influenced by many factors, such as economic, socio-cultural, educational, and other factors. In the environment, from the several factors above, it can be seen that there are many possible causes, one of which is the lack of intake of nutritious food and additional food during adolescence, pregnant women, and up to toddlers.To reduce the risk of stunting, of course, the latest and modern breakthroughs are needed, one of which is to provide knowledge and counseling from an early age related to stunting and nutritious food to prevent stunting and malnutrition in toddlers that lead to stunting. The purpose of this PKM is to minimize the occurrence of stunting at an early stage. The activity plan in this PKM is counseling and health checks for students at the Mulia Husada Health Vocational School Sumenep. The outputs to be achieved in this service are publication of service journals, and online mass media publications.